Estonia 1944–1946: From “Liberation” to Peacetime - Hiio, Toomas; Kaasik, Peeter (Institute of National Remembrance Review, 2023)
This paper is an overview of the situation in Estonia in 1944–1946. Estonia was occupied by the Soviet Union in 1940 and by Germany in 1941. In 1944, the Soviets returned. The attempt of re-establishing of the Estonian statehood in September 1944 failed, though a government in exile was formed in Sweden. Estonia lost about 20% of its population during 1940–1945. In the summer of 1941 more than 50,000 Estonians were mobilised to the Red Army or evacuated to the rear area of the Soviet Union. As part of the Sovietization plan, they were subsequently recruited and trained to fill in positions in the administration. In addition to that, a party and Soviet cadres were dispatched to Estonia by various Soviet offices and institutions. The real command and control of Estonia as well as other Baltic countries was firmly in the hands of special plenipotentiaries of the CC of the CPSU as well as the representatives of the NKVD and NKGB. Between 1944–1946, the Soviet terror continued. 20,000 individuals were arrested and most of them were to the GULAG camps outside of Estonia, more than 400 were deported to Siberia as Germans and their family members. Thousands of individuals were repatriated to Estonia from Germany and other European countries or transferred through a control-filtration camp in Estonia to the Soviet Union. Many corps and divisions of the Red Army as well as units of the Baltic Fleet were stationed in Estonia. Crimes committed by the military, from the robbery and plundering to rape and murder, were a serious problem not only for the population but also for the powerless local communist and Soviet authorities.